2020
DOI: 10.1177/0192513x20934829
|View full text |Cite
|
Sign up to set email alerts
|

The Health of African American Grandmothers Raising Grandchildren: A Growing Social Problem

Abstract: The study explored the experiences of African-American grandmothers residing in rural communities caring for their grandchildren, while suffering from chronic health issues. The research examined their physical and emotional health, physical functioning, well-being, social support, and resources of these grandmothers from a Family Development approach. Given the trends of providing care for a grandchild, it is widely recognized that caregivers may experience stress, burden, and the disruption of their well-bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It was also reported that couple parenting stress in foster families was related to the perceptions of both parent and their partners regarding their marriage and the co-parenting relationship ( Richardson & Futris, 2019 ). In addition, research revealed a variety of factors associated with caring stress including advanced age, poor overall health, and limited social life among grandparent carers ( Sprang et al, 2015 ; Woods, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also reported that couple parenting stress in foster families was related to the perceptions of both parent and their partners regarding their marriage and the co-parenting relationship ( Richardson & Futris, 2019 ). In addition, research revealed a variety of factors associated with caring stress including advanced age, poor overall health, and limited social life among grandparent carers ( Sprang et al, 2015 ; Woods, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…A few US studies focused on sociopolitical factors associated with carer stress emphasized poor governance and inadequate access to primary and specialty services for children and young people in care ( E.R. Barnett et al, 2017 ; Schneiderman et al, 2012 ; White et al, 2021 ; Woods, 2021 ), resulting in an unstable support system for carers ( Barrett et al, 2021 ). Although training was provided, a lack of post-training resources left carers feeling unsupported ( Barrett et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges of parental SUD for caregivers, protective factors may minimize the challenges. Woods (2021) found that spirituality and social supports were key coping mechanisms for caregivers of grandchildren. Dunfee et al (2021) suggest that religion and spirituality provide a sense of purpose, perspective, and coping among grandparent caregivers.…”
Section: Sud and Kinship Caregiversmentioning
confidence: 99%
“…Caregivers raising children are at greater risk of depression, social isolation, hypertension, insomnia, diabetes, and decreased physical and emotional well-being (Ge & Adesman, 2017; Hadfield, 2014; Woods, 2021). They are also faced with challenges of financial stress, lack of legal relationship with the child, inadequate housing and resources, and social isolation (Letiecq, Bailey, & Porterfield, 2008; Sharda, Sutherby, Cavanaugh, Hughes, & Woodward, 2019).…”
Section: Introductionmentioning
confidence: 99%